A Compound of Chinese Herbs Protects against Alcoholic Liver Fibrosis in Rats via the TGF-β1/Smad Signaling Pathway. (22nd April 2019) - Li, Xiaomeng; Liu, Yunjie; Yue, Wuyang; Tan, Yuefeng; Wang, He; Zhang, Lishi; Chen, Jinyao
Abstract : Alcoholic liver fibrosis (ALF) has become a major public health concern owing to its health impacts and the lack of effective treatment strategies for the disease. In this study, we investigated the effect of a compound composed of Chinese herbs Pueraria lobata (Willd.), Salvia miltiorrhiza, Schisandra chinensis, and Silybum marianum on ALF. An ALF model was established. Rats were fed with modified Lieber–Decarli alcohol liquid diet and injected with trace CCl4 at late stage. The rats were then treated with several doses of the compound. Biochemical and fibrosis-relevant parameters were measured from the sera obtained from the rats. Liver tissues were obtained for hematoxylin and eosin and Masson's trichrome staining. Matrix metalloproteinase-13 and tissue inhibitor of metalloproteinase-1 were determined by immunohistochemistry assays. The mRNA and protein expression levels of transforming growth factor- β 1 (TGF- β 1), Smad2, Smad3, and Smad7 on the livers were also measured by quantitative polymerase chain reaction and Western blot. Results showed that the compound treatment alleviated pathological lesions in the liver, decreased the serum levels of hyaluronan, laminin, and hydroxyproline, and diminished the expression of hepatic tissue inhibitor of metalloproteinase-1. Compound treatment also increased hepatic matrix metalloproteinase-13 expression and inhibited the TGF- β 1/Smad signaling pathway. In conclusion, the compound has a protective effect against ALF in rats, and an underlying mechanism is involved in the TGF- β 1/Smad signaling pathway.